Putting the "I" back in team - Ward, P.; Coutts, A. J.; Pruna, R.; McCall, A. (International Journal of Sports Physiology and Performance, 2018)
There is a common expression in sports that "there is no `I` in team." However, collectively, there is actually a very important "I" in sport teams—the individual athlete/player. Each player has his or her own unique characteristics including physical, physiological, and psychological traits. Due to these unique characteristics, each player requires individual provision—whether it be an injury risk profile and targeted prevention strategy or treatment/rehabilitation for injury, dietary regimen, recovery, or psychological intervention. The aim of this commentary is to highlight how 4 high-performance teams from various professional football codes are analyzing individual player data.